GREEN CONSUMERISM FROM THE PERSPECTIVE OF THEORY OF PLANNED BEHAVIOUR (CAHIERS MAGELLANES-NS, 2024)
Sustainability evolves from a simple concept into a critical global issue, the availability of environmental data underscores the need for collective action to mitigate the damage already done to the planet. In response, green consumers are increasingly making consumption choices from a wide range of sustainable products. Green consumerism is not only about purchasing eco-friendly products but also about adopting lifestyles that promote sustainability. This literature review aims to explore key aspects of green consumerism, including its theoretical foundations, drivers, challenges, and the role of digital platforms in shaping consumer behavior. y reviewing past studies, this paper summarizes key findings that contribute to a better understanding of green consumerism, particularly from the perspective of the theory of planned behavior, providing insights into how consumers’ intentions and behaviors are influenced by environmental, social, and psychological factors.